THE STRUGGLE FOR TEACHER PROFESSIONALISM IN A MANDATED LITERACY CURRICULUM - Costello, Marsha; Costello, David (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2016)
This article reports on a study investigating how elementary teachers experienced the literacy initiatives that have been implemented in schools across PEI over the past five years. Such initiatives included the implementation of standardized instructional and assessment materials across the board and the emphasis on consistency of program use, reporting, and evaluation. Data were gathered through an online survey and interviews. Throughout this study, issues of professionalism, emotional impact, and teacher resistance were explored. This article focuses specifically on the issue of teacher professionalism and its relationship with prescribed curriculum. Findings suggest that professionalism is challenged when teachers attempt to adhere to the fidelity of program processes. However, fidelity to the purpose of a program would allow for teacher decision-making and autonomy within the context of any given program or practice. PRÉSERVER SON PROFESSIONNALISME COMME ENSEIGNANT AU SEIN D’UN PROGRAMME DE LITTÉRATIE IMPOSÉ Ce texte présente les résultats d’un projet de recherche explorant la manière dont les enseignants de l’Île-du-Prince-Édouard ont vécu la mise en place d’actions en littératie au cours des cinq dernières années. Des données ont été recueillies à l’aide d’un sondage en ligne et d’entrevues. Au cours de l’enquête, des problématiques relatives au professionnalisme, aux impacts émotionnels et à la résistance des enseignants ont été explorées. Cet article s’attarde particulièrement à la question du professionnalisme enseignant dans le cadre d’un programme prescrit. Les résultats indiquent que lorsque les enseignants tentent de se conformer scrupuleusement aux processus du programme, ceux-ci le font au détriment de leur professionnalisme enseignant. Cependant, être fidèles aux objectifs du programme permettrait aux enseignants de préserver leur capacité à prendre des décisions et leur autonomie et ce, au sein de n’importe lequel programme ou milieu de travail.